X-Ray Diffraction Pattern of the Complex of 1,3,5-Hexachlorocyclotriphosphazene with Cobalt(II) Acetate - Jadon, S.P.S. (Asian Journal of Chemistry, 2016)
X-ray powder diffraction spectrum of the complex of 1,3,5-hexachlorocyclotriphosphazene with CoAc2, assigned as (PNCl2)2·CoAc2 quantitatively, suggested its Co2+ bridged hexadentated sandwich structure.